2013
DOI: 10.1002/lary.24107
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and histologic studies of olfactory outcomes after nasoseptal flap harvesting

Abstract: Olfactory impairment is not common after use of the NSF. Use of the cold knife in making superior incision may reduce tissue damage with better olfactory outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(67 citation statements)
references
References 21 publications
2
63
0
Order By: Relevance
“…Of the 19 biopsy specimens that contained olfactory epithelium, 10 had an influx of lymphocytes, macrophages, and eosinophils. Seven of these 10 patients (70%) had an abnormal UPSIT score (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31). Of the 12 patients with a normosmia (UPSIT score >35), only 3 (25%) had an inflammatory response.…”
Section: Inflammatory Changes To the Olfactory Epithelium In Chronic mentioning
confidence: 96%
See 2 more Smart Citations
“…Of the 19 biopsy specimens that contained olfactory epithelium, 10 had an influx of lymphocytes, macrophages, and eosinophils. Seven of these 10 patients (70%) had an abnormal UPSIT score (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31). Of the 12 patients with a normosmia (UPSIT score >35), only 3 (25%) had an inflammatory response.…”
Section: Inflammatory Changes To the Olfactory Epithelium In Chronic mentioning
confidence: 96%
“…The heat dispersion when using cautery may cause unintentional damage to the surrounding mucosa compared with a cold knife. 18 In a small cohort of 15 patients, Kim and colleagues 18 reported that 0 of 8 patients had a worsened BTT with cold knife compared with 1 of 7 with monopolar cautery 3 months after surgery. However, there was no significant reduction in the mean BTT or CCSIT olfactory tests in either of the groups.…”
Section: Perioperative Considerations In the Endonasal Approach To Thmentioning
confidence: 98%
See 1 more Smart Citation
“…However, our previous experience of development of the nasoseptal flap during endoscopic pituitary surgery provided us confidence that an additional incision can be made safely by using a cold knife. 8 As shown above, no significant olfactory injury occurred by our modified technique. Additionally, no other significant sequelae related to this modification were observed, including intraoperative or postoperative bleeding, delayed wound healing, synechia, and nasal septal perforation.…”
Section: Discussionmentioning
confidence: 90%
“…Comparison with studies reporting expanded techniques that intentionally transverse the posterior cribriform area do not allow a good comparison of olfactory disturbance because the olfactory morbidity is anticipated as a result of this approach. 18 Kim et al described differing outcomes based on cold dissection versus electrocautery, 19 noting that olfactory impairment was uncommon and reported in only one patient with impairment in their series. The premise that thermal injury might contribute highlights the fact that a defined area of olfactory-bearing septal mucosa exists.…”
Section: Discussionmentioning
confidence: 99%